CONNECTIVISM AS A FACTOR IN THE DEVELOPMENT OF SYSTEMS OF LOWER SECONDARY EDUCATION IN INFORMATICS - BUDÍNOVÁ, Vendula (Trends in education, 2017)
This paper deals with a dissertation on the topic Connectivism as a determinant of development of lower secondary education in computer science. The concept of connectivism is increasingly appearing in the conditions of Czech schools, and it is manifested, for example, through the increasing use of social networks in education. This issue becomes increasingly up-to-date with regard to the general popularity of social networks, and we have decided to respond to this by implementing a research survey that reflects the use of these new media in education. The paper presents partial aims of the thesis, a description of the expected research design. The research will be divided into two parts, namely a questionnaire survey and an experiment. Data collection will be carried out in pupils of the second level of primary schools in the Olomouc, South Moravian and Zlín regions.
Keywords: connectivism; social networks; information literacy; information education